The Effect of Entrepreneurial Marketing on Marketing Performance in SMEs - Aditya Liliyan (Kusuma Negara Business School, 2020)
The purpose of this research is to determine the level of entrepreneurial marketing carried out by SMEs and to contribute to literature and conceptual models on the effect of entrepreneurial marketing on marketing performance. The sample in this study were SMEs in the handicraft sector in Rembang, Central Java. The number of samples studied was 200 samples. The sampling technique used purposive sampling. The sample criteria are MSMEs that have been running a business for at least 3 (three) years. This is because in measuring the dimensions of marketing performance there are several indicators of the level of achievement of marketing performance each year, at least for a minimum of 3 years it can be seen the marketing performance of these SMEs. Data analysis using regression modeling. The results showed that entrepreneurial marketing has an effect and is significant on SMEs marketing performance handicraft sector in Rembang.